Treatment of Traumatised Sexuality - Almås, Elsa; Benestad, Esben Esther Pirelli (Frontiers in Psychology, 2021)
Based on therapeutic meetings with individuals who have experienced sexual violence and abuse, the challenge is how do we help these couples to establish sexual relationships on their own terms, without interference of defence or coping strategies they have used to protect themselves against the overwhelming experiences of violence or abuse in the past? This article will focus on therapeutic work with such couples and how to interact with them and support their efforts to establish satisfying sexual relationships, based on sexological experience as well as experience from work with traumatisation. The basis for our treatment is a modified version of William Masters and Virginia Johnson’s approach. The technique of sensate focus is central, modified by trauma theory, including the understanding of dissociation, and the need to integrate memories from different levels: somatic, emotional, and cognitive. The traumatised client needs special attention to the experiences of predictability and safety and respect due to their history of being transgressed against. The therapists must be aware of the issue of dissociation; different dissociated inner parts can play different roles in the interaction between client and therapist. While couples therapy is a necessary frame for this therapy, the therapist often needs to work with issues unique to each individual. Each partner must be able to identify their own responses and their own sexual needs and preferences. It may therefore be valuable to have a co-therapist. The central goal is for the clients to identify responses to stimulation as a here and now experience in a setting that feels safe and welcome.